Single Platelet-Rich Plasma Injection for Early Stage of Osteoarthritis of the Knee - Martini, Liborio Ingala; Via, Alessio Giai; Fossati, Chiara; Randelli, Filippo; Randelli, Pietro; Cucchi, Davide (Joints, 2017)
Purpose The purpose of this study was to determine the safety efficacy and outcomes of platelet-rich plasma (PRP) intra-articular injections for early stages of knee osteoarthritis (OA).Methods Twenty-five patients affected by grade I and II knee primary OA according to the Kellgren–Lawrence scale received a single intra-articular PRP injection. Patients were prospectively evaluated for 6 months. Visual analog scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Knee injury and Osteoarthritis Outcome Score (KOOS) scoring scales were used to evaluate clinical outcomes. Wilcoxon signed rank test was used to evaluate significance of improvement of WOMAC, KOOS, and VAS scores.Results Twenty-one patients completed 6-months follow-up. The median WOMAC score improved from 29.1 points (range: 17.4–60.4; standard deviation [SD] = 13.0) at baseline to 42.41 (range: 24.3–71.2; SD = 12.5) at final follow-up. Improvements in median KOOS and VAS score have been also found, from 37.49 points and 64.2 mm before injection to 59.71 points and 42.8 mm, respectively. All these improvements were statistically significant (p < 0.05). No adverse reactions have been observed.Conclusion Treating knee OA with PRP injection is safe. A single dose of PRP seems to be effective in managing pain and improving quality of life in patients with low-grade knee OA.Level of Evidence Level IV, therapeutic case series.
Keywords: platelet-rich plasma; growth factors; knee; osteoarthritis; intra-articular injection